Modeling the cost-benefit of nerve conduction studies in pre-employment screening for carpal tunnel syndrome - Bradley Evanoff; Steve Kymes (Nordic Association of Occupational Safety and Health (NOROSH), 2010)
OBJECTIVE: The aim of this study was to evaluate the costs associated with pre-employment nerve conduction testing as a screening tool for carpal tunnel syndrome (CTS) in the workplace. METHODS: We used a Markov decision analysis model to compare the costs associated with a strategy of screening all prospective employees for CTS and not hiring those with abnormal nerve conduction, versus a strategy of not screening for CTS. The variables included in our model included employee turnover rate, the incidence of CTS, the prevalence of median nerve conduction abnormalities, the relative risk of developing CTS conferred by abnormal nerve conduction screening, the costs of pre-employment screening, and the worker's compensation costs to the employer for each case of CTS. RESULTS: In our base case, total employer costs for CTS from the perspective of the employer (cost of screening plus costs for workers' compensation associated with CTS) were higher when screening was used. Median costs per employee position over five years were US$503 for the screening strategy versus US$200 for a no-screening strategy. A sensitivity analysis showed that a strategy of screening was cost-beneficial from the perspective of the employer only under a few circumstances. Using Monte Carlo simulation varying all parameters, we found a 30% probability that screening would be cost-beneficial. CONCLUSIONS: A strategy of pre-employment screening for CTS should be carefully evaluated for yield and social consequences before being implemented. Our model suggests such screening is not appropriate for most employers.